Feio não é bonito? experiências com a produção de arte infantil em um espaço de educação não-formal - Magalhães, Zilpa Maria de Assis (2013)
This research leans over Vivekinha, a not formal art/education space, with children classes of four to ten years old, located at the east zone of São Paulo city. The principal objective of this text is to analyze some experiences developed at Vivekinha, during the last six years of work. For this, the study reflects on the conditioning danger, that several times are present through preconceptions like pretty and ugly , right and wrong , in which many art conceptions are hidden. Generated at the mercy of different pedagogical chains, many of them alive and operating until today, this text examines some of them through the light of Brazil Art Education History. This research indicates positive results to the formulated hypothesis, revealing that Vivekinha has contributed to form the frequent children in this space, as well as some next familiar of them. The work defends the Idea that all educations (formal, informal and not formal) needs to articulate itself, aiming at a more integrated infancy development, to make possible the construction of production and attribution of senses systems to the world and to the life. The main theoretical references used in the text are the studies of Art Sociology, from Pièrre Bourdieu, and the researches on Brazilian Art/Education, from Ana Mae Barbosa, anchored in the following categories: perception, learning, formation, citizenship and not formal education.